Analisis Putusan Hakim Pengadilan Agama Terhadap Harta Bersama Yang Menjadi Tanggungan Kredit Di Bank Pasca Perceraian (Studi Putusan Nomor 277/PDT.G/2022/PA.PLG) - Jupriyanto (Lex Stricta : Jurnal Ilmu Hukum, 2024)
A legal marriage will certainly cause their property to merge into one. Thus, joint property, or shared property, automatically exists within the family. The normative legal method, using laws and court decisions, is employed in this research. The research findings indicate that Article 37 of the Marriage Law and Article 97 of the Compilation of Islamic Law state that each partner has half of the joint property unless the marriage agreement stipulates otherwise.